(untitled) (International journal of artificial intelligence, 2026)
The article comprehensively studies the metaphorical nature of medical terms in Latin. The purpose of the article is to identify and analyze Latin terms in medical terminology. As a research methodology and research materials, Latin terminology dictionaries, as well as terms selected from Latin textbooks, were used. Descriptive, lexical-semantic, structural, and comparative methods of linguistic research were used in the analysis. The article conducted an etymological, semantic, and structural analysis of 50 medical terms. Based on etymological observations, 5 main groups of terms were classified: zoomorphic terms formed in the image of animals; terms based on a specific action; terms-mythologisms containing names from ancient mythology, as well as terms based on the similarity of external signs. This article studies the structure and origin of some Latin terms related to medical terminology. According to the results of the analysis, examples of metaphorical nature were identified among Latin medical terms.